Getting StartED with Windows Live Movie Maker - Kelly, James Floyd; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Windows Live Movie Maker is a small but powerful movie editing application from Microsoft. It is a complete rewrite of the old Movie Maker software with a new audience in mind. The focus of this new edition is on giving you the power to quickly create movies and slideshows to share with your friends and family. The movies can be a combination of your favorite pictures and home movies set to your own soundtrack. You can add cool effects to transition between scenes, and captions to add a narrative to your movie. With Movie Maker, users can: Edit digital video and photos, including adding music and narration Apply animation effects to videos and photos Create DVDs for personal use, including menu systems for navigation
Windows Live Movie Maker -- Getting Started with AutoMovie -- Working with Video -- Working with Audio -- Working with Animations -- Playing with Visual Effects -- Working with Text -- Saving a Movie -- Publishing a Movie -- Creating a DVD -- Tips & Advice.
Keywords: Computer science; Computer Science; Programming Techniques